Effect of lime application on soil respiration is modulated by understory vegetation in subtropical Eucalyptus L’Hér. plantations - Liu, Juan; Li, Rui; Xu, Jianhong; Fu, Shenglei; Wan, Songze (Frontiers in Forests and Global Change, 2023)
Lime application and understory plant clearance are two common forest management methods employed to increase plantation productivity in subtropical regions. However, the effect of these two management methods, or their combination, on soil respiration in forest plantation settings is still not fully understood. Here, a field experiment was conducted to determine how lime application, understory clearance, and their combination, would impact total soil respiration (Rs), autotrophic respiration (Ra), and heterotrophic respiration (Rh) in a Chinese subtropical Eucalyptus plantation. Changes in soil microclimate and microbial community (PLFAs), as well as Eucalyptus fine root biomass were also assessed. Lime application stimulated Rh, but decreased Ra of understory vegetation (primarily Dicranopteris dichotoma), thus consequently inhibiting Rs. Understory clearance also reduced Rs, primarily due to reductions in soil PLFAs and associated Rh, and Ra of understory vegetation. Since the increase in Rh induced by lime application was greater than the decrease in Rh caused by understory clearance, the combination of lime application and understory clearance decreased Rs primarily by reducing understory root respiration. Our observations suggest that understory plants can modulate the effect of lime application on Rs, highlighting the important role of understory vegetation in regulating soil carbon cycling in subtropical Eucalyptus plantations. We concluded that the potential interactive effects should be considered in developing management practices that optimize the yield and sustainability of subtropical plantations.